2015
DOI: 10.1039/c5dt00931f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DNA/BSA interactions and anticancer activity of achiral and chiral copper complexes

Abstract: Six novel copper(ii) complexes of [CuCl]ClO4 (), [Cu(acac)]PF6 (), [CuCl]2(PF6)2 (), [CuCl]2(PF6)2 (), [Cu(acac)]PF6 () and [Cu(acac)]PF6 (), ( = 1-naphthyl-N,N-[bis(2-pyridyl)methyl]amine, = R/S-1-naphthyl-N,N-[bis(2-pyridyl)methyl]ethanamine, acac = diacetone) were synthesized to serve as artificial nucleases. All complexes were structurally characterized using X-ray crystallography. The crystal structures showed the presence of distorted square-planar CuLCl (, and ) and distorted tetragonal-pyramidal CuL(ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 69 publications
0
28
0
1
Order By: Relevance
“…Therefore, many novel metal complexes have been investigated and screened, and some of them are already in clinical trials [3,4]. Indeed, the cytotoxicity effect of metal complexes-mediated is generally accepted to result from their binding and cutting interaction with DNA, which leads to cell cycle arrest, apoptosis and the regeneration of cancers' DNA [5,6]. Even though the mechanism of antitumor activity exist diverse signaling pathways, DNA is the primary intracellular target of anticancer drugs, so the interaction between small molecules and DNA can often cause DNA damage in cancer cells, blocking the division of cancer cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many novel metal complexes have been investigated and screened, and some of them are already in clinical trials [3,4]. Indeed, the cytotoxicity effect of metal complexes-mediated is generally accepted to result from their binding and cutting interaction with DNA, which leads to cell cycle arrest, apoptosis and the regeneration of cancers' DNA [5,6]. Even though the mechanism of antitumor activity exist diverse signaling pathways, DNA is the primary intracellular target of anticancer drugs, so the interaction between small molecules and DNA can often cause DNA damage in cancer cells, blocking the division of cancer cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As complex 1 is chiral (complex 1 crystallizes in chiral space group) and complex 2 is achiral, it may be concluded that the chirality of complex 1 played very significant role to binding of chiral DNA molecule. It could also be found in literature that when two complexes were otherwise similar structurally, a chiral complex had a greater affinity for DNA …”
Section: Description Of Structuresmentioning
confidence: 86%
“…The exact methods and parameters of X‐ray crystallography used for the measurements of the structures are similar to our reported article . Single‐crystal X‐ray diffraction data of complexes 1 and 2 were collected at 113(2) K on a Bruker Smart 1000 CCD diffractometer using Mo‐Kα radiation (λ = 0.71073 Å) with the ω scan technique.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the selection of metal centers, the rational design of ligands is also crucial for the metal‐based antitumor agents. In this case, polyquinoline‐based ligands have gained extensive attentions, their complexes have been widely studied and showed superior DNA affinity and biological activity . This is partly due to the N atoms in quinoline moieties serving as coordination sites can stabilize metal ions at various valence states.…”
Section: Introductionmentioning
confidence: 99%